Risk map area plans (2016)
Using the methodology for risk management of the Administrative Department of Public Service it is wanted that through a sequence of steps to establish a risk matrix to implement in the area of plans so this minimizes risk and investigating the causes of potential unwanted events and the consequences they can produce. To set this matrix institutional preliminary information will be reviewed, mission, vision, strategic objectives, risk policy, then the risk, organizational strategic context, the process that includes it, its purpose, scope is identified, it will be held assessment, analysis, review of causes and consequences and establishment of actions, indicators and variables for measurement will be established , ending with the establishment of stock assessment, monitoring and monitoring for further disclosure.